Pendekatan Diagnosis Anemia pada Pasien dengan Penyakit Ginjal Kronik - Alif Fernanda Putra; Yusuf Aulia Rahman (MAJORITY, 2022)
Globally, anemia occurs in 1.62 billion individuals or around 24.8% of the population. In Indonesia, anemia occurs in about 15.4% of the population. Anemia is often a problem with misdiagnosis and inaccurate management. The male patient presents with weakness since the last month. The patient began to feel symptoms of hypertension (220/110 mmHg) at 3 months ago accompanied by tightness, itching in the body, weakness and pale days, swelling almost all over the body, and decreased urine. On physical examination, there was hypertension (160/90 mmHg), the conjunctival was anemic and on the palpebrae, superior and inferior limbs there was pitting edema. On supporting examination, it was obtained patient with normocytic and normochromic anemia Hb 5 g/dL, erythrocyte 1.8 million/μL, hematocrit 15%, LED 90 mm/hour, ureum 486 mg/dL, creatinine 39.28 mg/dL, calcium 4.7 mg/dL, chloride 92 U/L, sodium 124 mmol/L, and potassium 6.6 mmol/L. USG of the abdomen shows the results of bilateral chronic kidney disease. Management of anemia in patients needs to be holistic considered starting from the causes and the choice of therapy used in order to reduce morbidity and mortality and improve the patient's quality of life. This journal will explain the approach to anemia through illustrations on case of patient with anemia in chronic kidney disease.